Radiation dose measurements in coronary CT angiography - Sabarudin, Akmal; Sun, Zhonghua (Beijing Baishideng BioMed Scientific Co., Ltd, 2013)
Coronary computed tomography (CT) angiography is associated with high radiation dose and this has raised serious concerns in the literature. Awareness of various parameters for dose estimates and measurements of coronary CT angiography plays an important role in increasing our understanding of the radiation exposure to patients, thus, contributing to the implementation of dose-saving strategies. This article provides an overview of the radiation dose quantity and its measurement during coronary CT angiography procedures.